2018
DOI: 10.2147/ott.s164033
|View full text |Cite
|
Sign up to set email alerts
|

Multiple biological functions of transcription factor 21 in the development of various cancers

Abstract: Transcription factor 21 (TCF21) is a basic helix–loop–helix transcription factor that binds to DNA and regulates cell differentiation and cell fate specification through mesenchymal–epithelial transition during development. The TCF21 gene is epigenetically inactivated in many types of human cancers and exerts a wide variety of functions, including the regulation of epithelial–mesenchymal transition, invasion, metastasis, cell cycle, and autophagy. This review focuses on research progress in relation to the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 68 publications
1
11
0
3
Order By: Relevance
“…For instance, the mapped loci showing co-localization of AP-1 and TCF21 are enriched for genes that contribute to VEGF , TGFβ , EGF , Hippo, focal adhesion, and cell cycle biological processes (Additional file 1: Figure S4H). These terms are well known to associate with various forms of cancer, and the data presented here are consistent with both the involvement of AP-1 and TCF21 interactions in the biology of the tumor cell, since TCF21 is a well-known tumor suppressor [59], as well as the angiogenic processes that support tumor growth and expansion [60, 61].…”
Section: Discussionsupporting
confidence: 82%
“…For instance, the mapped loci showing co-localization of AP-1 and TCF21 are enriched for genes that contribute to VEGF , TGFβ , EGF , Hippo, focal adhesion, and cell cycle biological processes (Additional file 1: Figure S4H). These terms are well known to associate with various forms of cancer, and the data presented here are consistent with both the involvement of AP-1 and TCF21 interactions in the biology of the tumor cell, since TCF21 is a well-known tumor suppressor [59], as well as the angiogenic processes that support tumor growth and expansion [60, 61].…”
Section: Discussionsupporting
confidence: 82%
“…The helix-loop-helix (HLH) family of transcription factors possesses highly conserved bipartite domains for DNA binding and protein-protein interactions, which is pivotal in various developmental processes, covering myogenesis, neurogenesis, and hematopoiesis (Jiang and Yang, 2018). The HLH family members are divided into seven families according to tissue distribution, dimerization ability, and DNA binding specificity (Massari and Murre, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The HLH family members are divided into seven families according to tissue distribution, dimerization ability, and DNA binding specificity (Massari and Murre, 2000). Transcription factor 21 (TCF21, 6417bp)-also known as Pod1, bHLHa23, or Capsulin-encodes a transcription factor belonging to the cell-type-specific class II basic helix-loop-helix (bHLH) family at chromosome 6q23.2 (Jiang and Yang, 2018). Moreover, TCF21 is specific for mesoderm and is expressed in the embryos' mesenchymal derived tissues, such as the epicardium, lung, intestine, gonad, and kidney (Plotkin and Mudunuri, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The activation of TCF21 by long ncRNA TCF21 antisense RNA-inducing demethylation (TARID) by induction of promoter demethylation. Promoter of TCF21 in third CpG guides the TARID transcription, thereby inducing the DNA demethylation (TET protein-dependent) resulting TCF21 transcriptional activation and interaction of TARID to promoter of TCF21 , which inducts GADD45A/TDG to base excision repair (BER) for demethylation processes 29 . A recent study on TCF21 revealed the expression of TCF21 in normal lung airways with the observation of aberrantly methylated and silenced in majority of non-small lung carcinomas 30 .…”
Section: Resultsmentioning
confidence: 99%